Self-Hypnosis sebagai Metode Trauma Healing - Yanuarizky, Almaida (Trends in Applied Sciences, Social Science, and Education, 2023)
Hypnosis is often misunderstood by the wider community, because most of this hypnosis is used for needs that have no benefit which even invites crime, even though this hypnosis can be used for more useful things if the technique can be done correctly, especially in hypnosis for yourself, knowledge is really needed in In society, one of the uses of self-hypnosis is as a trauma healing method. The aim of this research is to find out and describe self-hypnosis, which is a method of trauma healing. This research was carried out using library research in which the researcher researched by reading trusted sources, one of which was books. What was discovered about how self-hypnosis is that it can function to self-hypnosis of individuals who experience trauma after an undesirable event occurs to that individual.